Gender equality in Mary Wollstonecraft's thought: Aisyiyah's perspective as a women's movement for advancement - Era Nur An-nisaa’ Candra; Mohammad Zakki Azani (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Gender equality remains a pertinent issue across diverse social contexts, encompassing Western and Islamic teachings. Mary Wollstonecraft, a prominent advocate for gender equality in the West, contended that women should possess individual freedom without male domination. In Indonesia, Aisyiyah, a progressive women's movement, posits that gender equality should be examined not only through religious and spiritual lenses but also through political, economic, and educational dimensions. This research employs a qualitative approach, utilizing a literature study method to analyze various books, articles, and reports relevant to the topic. Despite their differing cultural and religious perspectives, both Aisyiyah and Mary Wollstonecraft assert that education is fundamental to achieving gender equality. This article explores Aisyiyah's perspective as a progressive women's movement to critically analyze Mary Wollstonecraft's concept of gender equality, which is often perceived as being incompatible with the Islamic worldview. The findings of this study aim to offer an Islamic perspective from Aisyiyah that addresses the challenges posed by Western secular thought.   Kesetaraan gender merupakan topik yang selalu relevan dalam berbagai konteks sosial, baik di Barat maupun dalam ajaran Islam. Salah satu tokoh kesetaraan gender di Barat, Mary Wollstonecraft yang memperkasai perjuangan perempuan untuk kesetaraan gender berpendapat bahwa perempuan perlu memiliki kebebasannya secara individu tanpa diatur oleh laki-laki. Aisyiyah sebagai gerakan perempuan berkemajuan di Indonesia menyoroti kesetaraan gender tidak hanya dapat dilihat dari perfektif agama dan spiritual, tetapi juga dari berbagai aspek lain seperti politik, ekonomi dan pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan, yang berfokus untuk menganalisis berbagai buku, artikel, dan laporan yang memiliki keterkaitan dengan topik yang dibahas. Meskipun keduanya mengusung pandangan yang berbeda dalam konteks budaya dan agama, baik Aisyiyah maupun Mary Wollstonecraft berpendapat bahwa pendidikan adalah kunci utama untuk mencapai kesetaraan gender. Artikel ini menyajikan perspektif Aisyiyah sebagai gerakan perempuan berkemajuan untuk menganalisis konsep kesetaraan gender menurut Mary Wollstonecraft, yang dianggap tidak sesuai dengan pandangan hidup Islam. Temuan dalam kajian ini diharapkan dapat memberikan pandangan hidup Islam dari perspektif Aisyiyah yang mampu menjawab tantangan pemikiran Barat sekuler.